1999
DOI: 10.1366/0003702991945443
|View full text |Cite
|
Sign up to set email alerts
|

Surface-Enhanced Fluorescence on SiO2-Coated Silver Island Films

Abstract: Fluorescence is one of the molecular spectroscopic properties that is enhanced by placing the molecule on the rough surface of a coinage metal. The surface-enhanced fluorescence (SEF) can be directly observed in steady-state fluorescence experiments. The observations are the results of a delicate balance between the enhanced emission and the quenching due to energy transfer to nonradiative surface plasmons. In the present report, SiO2-coated silver films were fabricated at varying dielectric thickness. The sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
95
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(102 citation statements)
references
References 14 publications
(15 reference statements)
6
95
0
1
Order By: Relevance
“…Studies of SiO2 dielectric coating of plasmon active (fractal) thin gold or silver metal layers have been reported [26][27][28][29]. These studies demonstrated that using thin coating (e.g.…”
Section: Papermentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of SiO2 dielectric coating of plasmon active (fractal) thin gold or silver metal layers have been reported [26][27][28][29]. These studies demonstrated that using thin coating (e.g.…”
Section: Papermentioning
confidence: 99%
“…The schematic shows that the array possesses a 70 nm inter rod distance, a rod diameter 35 nm and rod height of 200 nm. The preparation of the Au nanorod arrays are described elsewhere [27]. In brief, the sample was made on a glass substrate base.…”
Section: Papermentioning
confidence: 99%
“…The interaction of fluorophores with metallic particles has been the subject of several publications [27][28][29]. There is reasonable agreement that the maximal enhancements occur about 100 Å from the surface, but some publications report the optimal distance to be as large as 600 Å [30].…”
Section: Distance-dependent Enhancementmentioning
confidence: 99%
“…Because of these applications, it is important to understand these interactions in terms of the effects of chemical nature, size, shape of the nanostructure, and its distance from the interrogating fluorophore. [15][16][17][18][19] A detail understanding of the MEF and its distance dependence nature is vital for its potential application in biomedical sensing. [20][21][22] Layer-by-layer (LbL) assembly [23][24][25][26][27][28][29][30][31][32][33][34][35][36] is based on the sequential adsorption of polycations and polyanions from dilute aqueous solution onto a solid substrate as a consequence of the electrostatic interaction and complex formation between oppositely charged polyelectrolytes.…”
Section: Introductionmentioning
confidence: 99%